Socioeconomic Distress Does Not Influence Postoperative and Patient-Reported Outcomes Following Surgical Management of Insertional Achilles Tendinopathy with Haglund Deformity - Joydeep Baidya BS; Nana Amponsah BA; Kush Mody MD, MBA; Amy Nghe BA; Omar Sarhan BS; Nate Rose BS; Tyler West BS; David Pedowitz MD; Joseph Daniel DO; Selene Parekh MD, MBA (Foot & Ankle Orthopaedics)
Submission Type: Achilles Tendinosis Research Type: Level 3 - Retrospective cohort study, Case-control study, Meta-analysis of Level 3 studies Introduction/Purpose: Insertional Achilles Tendinopathy (IAT) with calcaneal exostosis, or Haglund deformity (HD), can result in debilitating heel pain. The first course of treatment is nonsurgical modalities including physical therapy, shoe wear modification, and injections. While outcomes following surgery for IAT with HD have previously been explored, there is a paucity of literature investigating the impact of socioeconomic factors. Distressed Communities Index (DCI) is a metric that captures neighborhood-level socioeconomic distress utilizing zip codes, where higher scores indicate greater distress in the community. Previous studies have demonstrated higher DCI to be associated with adverse outcomes following a number of orthopedic surgical procedures. Therefore, this study aimed to identify the impact of DCI as a proxy for socioeconomic distress on outcomes after surgical management of IAT with HD. Methods: Patients > 18 years of age who underwent surgical management for IAT with HD at a tertiary care center from 2017-2022 were reviewed. Patients’ zip code of residence was queried and matched to DCI score and quintile provided by the Economic Innovation Group. Demographic and surgical characteristics including age, race, sex, BMI, Charlson Comorbidity Index (CCI), length of stay, insurance, marital status, diabetes, smoking status, history of injury, time to surgery, history of ankle surgery, preoperative physical therapy, steroid injection, and bracing, and usage and type of graft for repair. Outcomes of interest were readmission, revision, debridement, Achilles tendon retear, manipulation under anesthesia, time to weightbearing, postoperative physical therapy, steroid injection, and bracing. Patient-reported outcome of Foot and Ankle Ability Measure (FAAM) was collected preoperatively and at 1- and 2-year postoperatively. ANOVA or Kruskall-Wallis tests were used for continuous variables. Chi-Square or Fisher's Exact tests were used for categorical variables. Results: A total of 165 patients who met inclusion criteria were identified. Of these, 61, 49, 30, 12, and 13 patients were in the prosperous, comfortable, mid-tier, at-risk, and distressed quintiles, respectively. The proportion of females in the distressed quintile (92.3%) was significantly different but all other demographic and surgical variables were comparable between groups. Patients in the distressed group experienced the highest rate of 30-day readmission (23.1%), revision (15.4%), and debridement (7.69%), and those in the at-risk group experienced the greatest improvement in FAAM scores at 1-year postoperatively, but these were not significantly different from the remaining groups. All other surgical and patient-reported outcomes were similar across quintiles. Conclusion: Patients residing in distressed communities as delineated by the DCI were not found to experience any additional burden of adverse postoperative events or patient-reported outcomes up to 2 years following surgery for IAT with HD compared to their counterparts in other DCI quintiles. Further research should be aimed at examining the impact of socioeconomic factors on a more granular scale in order to identify potential risk factors for complications and methods of reducing them.